An On‐Chip Break Junction System for Combined Single‐Molecule Conductance and Raman Spectroscopies. (25th May 2020) - Jeong, Hyunhak; Li, Haipeng B.; Domulevicz, Lucas; Hihath, Joshua
Abstract: Systems that are capable of robustly reproducing single‐molecule junctions are an essential prerequisite for enabling the wide‐spread testing of molecular electronic properties, the eventual application of molecular electronic devices, and the development of single‐molecule based electrical and optical diagnostics. Here, a new approach is proposed for achieving a reliable single‐molecule break junction system by using a microelectromechanical system device on a chip. It is demonstrated that the platform can (i) provide subnanometer mechanical resolution over a wide temperature range (≈77–300 K), (ii) provide mechanical stability on par with scanning tunneling microscopy and mechanically controllable break junction systems, and (iii) operate in a variety of environmental conditions. Given these fundamental device performance properties, the electrical characteristics of two standard molecules (hexane‐dithiol and biphenyl‐dithiol) at the single‐molecule level, and their stability in the junction at both room and cryogenic temperatures (≈77 K) are studied. One of the possible distinctive applications of the system is demonstrated, i.e., observing real‐time Raman scattering in a single‐molecule junction. This approach may pave a way to achieving high‐throughput electrical characterization of single‐molecule devices and provide a reliable platform for the convenient characterization and practical application of single‐molecule electronic systems in the future. Abstract : A novel on‐chip single‐molecule break junction system based on a microelectromechanical system (MEMS‐BJ) is fabricated using a conventional semiconductor manufacturing process on a silicon‐on‐insulator wafer. Compared with conventional single‐molecule junction testbeds, the MEMS‐BJ system provides better optical accessibility and scalability but requires a smaller apparatus, which makes it a reliable platform for the convenient characterization and practical application of single‐molecule electronic systems.